2016
DOI: 10.3389/fmicb.2016.00496
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus: the Latest Newcomer

Abstract: Since the beginning of this century, humanity has been facing a new emerging, or re-emerging, virus threat almost every year: West Nile, Influenza A, avian flu, dengue, Chikungunya, SARS, MERS, Ebola, and now Zika, the latest newcomer. Zika virus (ZIKV), a flavivirus transmitted by Aedes mosquitoes, was identified in 1947 in a sentinel monkey in Uganda, and later on in humans in Nigeria. The virus was mainly confined to the African continent until it was detected in south-east Asia the 1980’s, then in the Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
192
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(203 citation statements)
references
References 163 publications
(264 reference statements)
3
192
0
8
Order By: Relevance
“…In one volunteer, a febrile illness of 4 days' duration developed 82 hours after subcutaneous inoculation of Zik a virus [12].…”
Section: Introductionmentioning
confidence: 99%
“…In one volunteer, a febrile illness of 4 days' duration developed 82 hours after subcutaneous inoculation of Zik a virus [12].…”
Section: Introductionmentioning
confidence: 99%
“…R1118, R324 = WCCREC TMPPLSFRAKDGCW [1] W1118, W324 =WCCREC TMPPLSFWAKDGCW [2] Q1118, Q324 = WCCREC TMPPLSFQAKDGCW [3] The mutation site in polyprotein amino acid 1118 (numerically NS1 amino acid 324) is depicted in red. The data and analysis presented here support and expand the data and analysis presented by Freire et al [15] and therefore suggest that the observed Shannon entropy may be associated with immunological activity.…”
Section: Journal Of Medical Microbiology and Diagnosismentioning
confidence: 99%
“…Zika virus (ZIKV) is a single-stranded, positive sense RNA virus [1]. The Zika virus polyprotein consists of precursors of three structural proteins (capsid, precursor membrane (prM) and envelope (E) protein) and seven major nonstructural proteins (NS1, NS2A, NS2B, NS3, NS4A, NS4B, and NS5) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Complications of Zika virus infection include Guillain-Barré syndrome and microcephaly in the fetus of pregnant women infected in the first trimester. Treatment is again primarily supportive with preventive measures, such as insect repellant and protective clothing, paramount in anyone travelling to areas where they might be exposed to Zika virus [54].…”
Section: Zikamentioning
confidence: 99%